Testing oral nicotine pouches versus nicotine replacement therapy for cigarette harm reduction in Appalachia: The ARISE study protocol - Wermert, Amy; Brasky, Theodore M.; Newton, Alison M.; Hinton, Alice; Curran, Hayley; Ferketich, Amy K.; Carpenter, Matthew J.; Shields, Peter G.; Tomko, Patrick; Wagener, Theodore L.; Keller-Hamilton, Brittney (PLOS ONE, 2025)
Background With the highest cancer incidence and mortality rates in the country, rural Appalachia has experienced a decades-long health decline, due in part to high smoking rates. Cigarette smoking prevalence exceeds 30% in much of the region. Oral nicotine pouches (ONPs), which contain nicotine but no tobacco, present an unexplored opportunity to reduce cigarette smoking and cancer incidence. Objectives We outline the protocol for the Appalachian Research to Impact Smoking’s Effects (ARISE) study, a randomized controlled trial to determine whether ONPs affect cigarette smoking patterns short- and long-term, and to evaluate their abuse liability versus nicotine replacement therapy (NRT) in a large sample of Appalachian smokers (clinicaltrials.gov: NCT06763536). Methods Between 2025 and 2029, we will recruit 1,000 adult smokers living in rural Appalachian counties across 11 states. Participants will be identified via media outreach, mobile cancer screening, community events, and respondent-driven sampling, then randomized to ONP or NRT and complete four study phases: Baseline, Sampling, Switch, and Observation. In the Sampling phase, participants will receive varied flavors and nicotine strengths of their assigned product and select preferred options for use. During the Switch Phase, they will attempt to quit smoking and switch completely to their assigned product. The Observation phase will monitor tobacco use after discontinuation of study products. Study procedures will be conducted online and by mail, including surveys, expired carbon monoxide verification, and product delivery. The primary outcome is 7-day biochemically verified cigarette abstinence at the end of the Switch Phase. Secondary outcomes include switching rates, product appeal, craving, withdrawal, dependence, and purchases during the Observation phase. An intention-to-treat log-binomial regression model will estimate the effect of intervention assignment on cigarette abstinence. Conclusions Results will inform whether and how ONPs should be regulated, approached clinically, and used in public health interventions to reduce the burdens of cigarette smoking in Appalachia.